ANALISIS VARIAN ANGGARAN SEBAGAI PENGENDALIAN BIAYA PROYEK PADA PT KREASI TIGA PILAR (POSITIVE) STUDI UNTUK PROYEK SONY STORE TAHUN 2014 – 2016 - Hayuningtyas Pramesti Dewi, SE., Ak., M.Ak., CA; Sari Retno Setiowati (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2018)
This study tries to analyze the budget difference with the realization of activities at PT Kreasi Tiga Pilar during 2014 until 2016. The activity analyzed is the cost of making Sony Store project in three different places. The difference (variance) of the project cost is calculated from the variance of raw material costs, direct labor costs and overhead costs. The results of the study show that during the year 2014 to 2016 there is still a variance between the budget with the realization of the implementation of activities that are potentially unprofitable for the company.